Analisis Rantai Pasok (Supply Chain) Beras Payo Di Kecamatan Gunung Raya, Kabupaten Kerinci - Andari Mukhtasida, Bunga; Napitupulu, Dompak; Edison, Edison (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2022)
Payo rice is one of the ancestral legacies of the Kerinci community which has been passed down from generation to generation to the Kerinci community. Payo rice supply chain analysis needs to be done to be able to calculate the level of market efficiency of the various links involved, so it can be seen the potential market access of payo rice which is scattered in various regions in Jambi Province. This study aims to 1) Knowing the description of the payo rice supply chain mechanism in Gunung Raya Sub-District, Kerinci District; 2) Analyzing the level of efficiency of Payo rice in Gunung Raya Sub-District. The determination of the location of this study was carried out with consideration that Gunung Raya District is an area that still produces Payo rice in Kerinci Regency. The sampling method used is nonprobability sampling. To find out the mechanism of payo rice supply chain, the determination of samples is taken based on purposive sampling and snowball sampling by setting one key person. The description and mechanism of the supply chain were analyzed using qualitative analysis methods within the framework of the Food Supply Chain Network (FSCN). And the analysis of the level of market efficiency uses a quantitative method with an operational efficiency analysis approach based on the measurement of marketing margins and the value of the farmer's share. The results of this study indicate that there are 4 channel patterns depicted in the payo rice supply chain mechanism in Gunung Raya District, each of which has a fairly good product flow, financial flow, and information flow. The perception of farmers, traders, and marketefficiency of the Payo rice supply chain has been efficient with a high farmer’s share value that is above 50%.